PENERAPAN STRATEGI MANAJEMEN KONFLIK DI LINGKUNGAN SEKOLAH: ANALISIS BERDASARKAN KAJIAN LITERATUR - Maharani, Rafika; Hanif, Ma’mun (Jurnal Manajemen Pendidikan, 2024)
This research aims to describe the implementation of conflict management strategies in the school environment based on a literature review. This research is qualitative research in the nature of library research where various books and other literature are used as the main source. Qualitative research is a research method that produces information in the form of descriptions and notes based on the text that is the focus of the research. Data collection uses the source search method and constructs it from various literature, for example books, journals and previous research results. Library materials are obtained through various references which are analyzed critically and in depth to strengthen arguments and ideas. The result of this research is that through an in-depth understanding of the literature review, we can detail concrete steps that can be taken by educational institutions to increase their capacity in managing conflict. In this way, schools can become spaces that not only provide quality education but also form good character and conflict resolution abilities in students. The literature review illustrates that implementing conflict management strategies in the school environment is an important step to increase harmony and effectiveness of educational institutions.